EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PADA SISTEM PENGAJUAN DAN PERSETUJUAN KREDIT PADA PT BANK PUNDI - Windy Adriana (JURNAL AKADEMIKA)
Credits is the one of main activities in the industries banking. In providing of facilities credits, the risk is so very high. To avoid, the necessary from accounting information system and controlling are adequate to guarantee the loan. The Background of the writing can be concluded that the accounting information system applied in the procedures for submission and provision of credit adequate, and eventhought the characteristics of accounting information systems that are usefulness, economy, reliability, customer services, capacity, simplicity,and flexibility. The elements of accounting information systems are the existence of human resources, equipment (computer), records (forms, journals, ledgers) and statements, must being in accounting information systems and as a resulted in useful required information by the PT Bank Pundi.